Answers

2015-03-27T09:02:40+05:30
SecA=1/cosA
secA(1-sinA)=1/cosA(1-sinA)=1/cosA-sinA/cosA=secA-tanA
WE HAVE AN IDENTITY THAT sec^2A-tan^2A=1
therefore SecA(1-SinA)*(SecA+tanA)=sec^2A-tan^2A=1
1 5 1
The Brainliest Answer!
2015-03-27T09:05:21+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
SecA(1-sin A)*(secA+tanA)=1
 LHS;
Converting everything to sinA and cosA;

=> (1/cosA)(1-sinA)(1/cosA+sinA/cosA)

Solving;
=>{ ( 1-sinA ) / cosA }{ (1+sinA)/cosA) }

Multiplying both the brackets

=>(1-sin²A)/cos²A

Since Sin²A+cos²A=1
so, cos²A=1-sin²A

=> cos²A/cos²A
=1 

hence, LHS= RHS

Thus Proved,

2 5 2